AN ANALYSIS OF DISCRIMINATION AND ITS EFFECT IN â€œELEMENTALâ€ (2023) MOVIE - Devyana, Natasya; Nugroho, Ardi (International Journal of Research on English Teaching and Applied Linguistics, 2024)
This research explores the role of animated films as a medium for addressing social issues, particularly discrimination, with a focus on the film â€œElementalâ€ (2023). Using a qualitative approach, the study analyzes discriminatory actions and their impacts on the three main characters: Barnie, Cinder, and Ember. Drawing on Dovidio and Essesâ€™ (2010) theory of discrimination and AyÃ³n's (2015) concept of effects, the research highlights parts of the film depicting discrimination and its physical and non-physical consequences. The result of the current study shows that different types of discrimination were portrayed in the movie through explicit and implicit actions as well as institutional and cultural biases. These findings indicate that animated films can effectively convey information about discrimination to various audiences, especially children, in a creative and easily understandable manner. This reaffirms that animated films serve not only as tools for ideological communication but also as agents of social change. The study also dissects the negative impacts of discrimination on the mental health and family functions experienced by the main characters. Through the analysis of discriminatory actions presented in dialogue, settings, and actions in the film, the research provides a profound understanding of the main characters' experiences in facing discrimination. In conclusion, this research reinforces the importance of using animated films as a tool for voicing social issues.